Підходи до розробки інформаційно-аналітичної системи для прийняття управлінських рішень на підприємстві - Ніколаєв, І. В.; Вишневська, В. А.; Жовновач, Р. І.; Nikolaiev, I.; Vyshnevska, V.; Zhovnovach, R. (ЦНТУ, 2019)
Враховуючи, що великій кількості виробничих підприємств України притаманна неефективність функціонування, пов’язана з недоліками в управлінні, обґрунтовано необхідність створення інформаційно-аналітичної системи прийняття управлінських рішень (ІАСПУР). Розроблено структуру локальної інформаційно-аналітичної системи прийняття управлінських рішень у режимі реального часу, що використовує комплекс моделей оцінки й аналізу стійкості функціонування підприємств у динаміці. Проаналізовано зміст етапів побудови інформаційно-аналітичної системи прийняття управлінських рішень з метою здійснення її програмної реалізації. Taking into account the fact that a large number of manufacturing enterprises in Ukraine are characterized by inefficient functioning due to weaknesses in management, was substantiated the necessity of creation of information-analytical system for managerial decision-making (IASMDM), which is designed to provide support for managerial decisions to improve the efficiency of the operation of the enterprise. Therefore, the purpose of the paper is to develop the structure of the information- analytical system for managerial decision-making using a set of economic and mathematical models. The structure of the local information-analytical system of managerial decision-making in real-time, using a set of models for estimating and analyzing the stability of the enterprise functioning in dynamics was developed. These models are based on the classical apparatus of the automatic control theory (ACT) and the logistic approach in economic systems. This approach opens the wide possibilities of a formal description of such complex systems as manufacturing enterprises and the application of well-known stability criteria to them – the algebraic Hurwitz criterion and the graph-analytical criterion of Mikhailov. The content of the stages of construction of the information-analytical system for managerial decision-making, which will allow its program implementation, is also considered and analyzed.
Approaches to the Development of Information-analytical System for Management Decision-making at the Enterprise
Keywords: інформаційно-аналітична система; ефективність функціонування; системи прийняття рішень; підприємство; управління; управлінські рішення; information-analytical system; efficiency of functioning; enterprise; management; management decisions; decision-making systems